Spatial Analysis of Landslide Hazard Mapping Using GIS And Weighted Overlay in Semarang Regency - Salafudin, Agus; Muta'ali, Lutfi; Saputra, Erlis (EL-JUGHRAFIYAH, 2025)
Semarang Regency is one of the regions included in the administration of Central Java Province. Aspect of potential disaster always consider in a good development. Landslide hazard analysis is necessary for regional planners to mitigate the disaster in the development area. This paper examines landslide hazard mapping in Semarang Regency. The method used is a geographic information system with weighted overlay analysis. The parameters used to assess landslide hazard are rainfall, slope, geology, soil type, and land use. The scoring and weighting of each parameter are based on expert opinion obtained from published research with contex-tualization to the condition of the study area. The results show that 0.29% of the area is cate-gorized as a very high landslide hazard zone, 17.74% of the area is classified as a high land-slide hazard zone, 61.66% as a medium landslide hazard zone, 18.91% as a low landslide haz-ard zone and 1.40% as a very low zone. The results of this study can be used as a reference and consideration for future regional development in order to create a balance between envi-ronmental sustainability and growth.